1996
DOI: 10.1007/bf01209033
|View full text |Cite
|
Sign up to set email alerts
|

The important prognostic value of Ki-67 expression as determined by image analysis in breast cancer

Abstract: A series of 191 female breast carcinomas (with long-term follow-up) were analysed immunohistochemically (with a monoclonal MIB1 antibody) for Ki-67 (a proliferation marker) expression with special reference to well-established prognostic factors and patient survival. Expression of Ki-67 was directly related to the S-phase fraction (P < 0.0001), the volume-corrected mitotic index (P < 0.0001), histological grade (P < 0.0001), the apoptotic index (P < 0.0001), oestrogen and progesterose receptor content (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
6
24
1
1
Order By: Relevance
“…Our ®nding of seven immunohistochemical pRB defect out of 79 examined tumours (9%) is somewhat lower than in other studies in breast cancer (Varley et al, 1989;Sawan et al, 1992;PietilaÈ inen et al, 1995) where frequencies have been between 20 and 30% using the same technique. These di erences could be caused by various immunostaining methods and evaluation procedures.…”
Section: Discussioncontrasting
confidence: 72%
“…Our ®nding of seven immunohistochemical pRB defect out of 79 examined tumours (9%) is somewhat lower than in other studies in breast cancer (Varley et al, 1989;Sawan et al, 1992;PietilaÈ inen et al, 1995) where frequencies have been between 20 and 30% using the same technique. These di erences could be caused by various immunostaining methods and evaluation procedures.…”
Section: Discussioncontrasting
confidence: 72%
“…In our study we found a significant influence of MIB-1 on disease-free survival in nodenegative, but not node-positive patients. Comparable results have been found in two other studies (Pietilainen et al, 1996;Querzoli et al, 1996), whereas one study has demonstrated an effect of MIB-1 on disease-free survival for both groups of patients (Seshadri et al, 1996). A difference in the prognostic value of MIB-1 for nodenegative and node-positive patients could be explained by more susceptibility for adjuvant (chemo)therapy in node-positive patients with high MIB-1 labelling index, whereas node-negative patients were not treated by adjuvant systemic therapy.…”
Section: Discussionsupporting
confidence: 50%
“…In general, the MIB-1 index also seems to be a prognostic factor sometimes even in multivariate analyses, but follow-up is generally rather short and/or the number of patients is low (Jensen et al, 1995;Domagala et al, 1996;Seshadri et al, 1996;Pietilainen et al, 1996;Veronese et al, 1996). Not many studies have been performed comparing the different methods of assessing the proliferative activity of a tumour.…”
mentioning
confidence: 99%
“…AI was 4.5(0.5)/mm 2 , compared with 15.4(1.1)/mm 2 in tumours with a mitotic index greater than 10/mm 2 (P<0.0001) . Other indicators of cell proliferation, such as Ki67 expression (Pietiläinen et al 1996, Ellis et al 1998, van Slooten et al 1998, also have been found to be highly significantly related to AI, in studies based on image analysis (Pietiläinen et al 1996) or conventional light microscopy (Ellis et al 1998, van Slooten et al 1998. In a series of 49 breast carcinomas, 84% of tumours in which the proportion of Ki67-positive cells was less than 20% also had an AI below the median value (0.77%); 61% of tumours in which there was more than 20% of Ki67-positive cells had AIs greater than that median value (P=0.001) (van Slooten et al 1998).…”
Section: Mitotic Index and Ki67 Expressionmentioning
confidence: 99%